Beyond Branding: The Dominant Role of Tourist Attractions and Digital Promotion in Driving International Revisit Intentions to Nusa Dua, Bali - Dayan Hakim Natigor Sihaputar; Ekos Albar; Irfani Fithria; Listri Herlina (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
Nusa Dua, Bali, is an integrated tourism area in South Bali, known for its international standards, luxury resorts, and a 4 km stretch of white-sand beach. The destination is also recognized for its sustainable tourism, having been designated an environmentally friendly